Estimación de parámetros de estabilidad para determinar la respuesta de híbridos de maíz (Zea mays L.) a ambientes contrastantes de Centro América Panamá y México - Córdova, Hugo S. (2016)
Genotype by environment interactions are extremely important when evaluating cultivars developed for diverse environmental conditions. Differences in environments and years can change the relative ranking of genotypes across environments. Thus, it is necessary to incorporatestability parameters to properly define the adaptation ofcultivars to given environments. The objective of this study was to determine the adaptation of maize hybrids developed by National Programs and private seed industries in Central Aroerica and the Caribbean. Thirty six (36) hybrids were evaluated across 151ocations during 1989 throughout North and Central America. Cultivar, performance and yield stability was analyzed using AMMI and Eberhart and Russell models. Hybrid HB-85 from ICTA yielded 5.7 t/ha, outyielding the local check H-5 by 34 %. In addition, this hybrid had excellent husk cover and minimal ear rot, and proved adapted to both favorable and unfavorable environments. Hybrid P-8802 from Panama also showed similar performance. The AMMI model identified the hybrids MAX-309, P-8812, P-88222, HB-85 and HB-87 as the most stable. Hybrids HB-85, HB-87, and HB-83M showed stability of grain yield (β1= 1, Sdi = 0) across 34 sites and 2 years. Good progress has been achieved in the production of hybrids adapted to adverse abiotic and biotic stresses for the Central American and Caribbean region. It is sllggested that the use ofthese new hybrids be encouraged to increase the productivity of maize in the region.